PENDIDIKAN KESEHATAN PENCEGAHAN DEMAM BERDARAH PADA SISWA SLTP DI PONDOK PESANTREN ISLAMIC BIN BAZ YOGYAKARTA - Errick Endra Cita; Supriyanto (ABDIMAS Madani, 2019)
Dengue Fever (DHF) can appear throughout the year and can affect all age groups. This disease is related to environmental conditions and community behavior. DHF causes deaths in the Southeast Asian region from 1990-2015 to have an increasing trend. The number of dengue morbidity in 2016 also increased from 2015, which was 50.75 to 78.85 per 100,000 population. Bantul district DHF incidence in 2016, the incidence of dengue cases rose when compared to 2015. In 2016 there were 2442 cases of dengue fever (IR 2.51%), while in 2015 there were 1441 cases (IR 2.51%) . The highest incidence of DHF cases in Bantul district occurred in the Kasihan II health center area of ​​227 cases. Efforts that can be made to prevent the incidence of dengue are health promotion carried out in all sectors including the establishment of a jumantik exterminator in families and schools. The method of health education that is used in this community service is by using audiovisual media. Measurement of knowledge is done qualitatively by giving questions in a straightforward and structured manner. The results of the evaluation of knowledge found that there was an increase in knowledge before after being given health education with indicators that the majority of students could mention preventive measures that could be taken for DHF.